Minimally invasive plate osteosynthesis (MIPO) in the treatment of the femoral shaft fracture where intramedullary nailing is not indicated - T. Apivatthakakul (2018)
The aim of this study was to examine the results of minimally invasive plate osteosynthesis (MIPO) of the femoral shaft fracture in patients where intramedullary nailing is contraindicated and evaluate the proper number of the screws for stable fixation. This was a retrospective study of 36 closed femoral shaft fractures which underwent MIPO using a conventional 4.5 broad dynamic compression plate (DCP) with 14-18 holes fixed with three or four screws in the proximal and distal fragments. Thirty-three fractures had bony union in 21.0 weeks (range, 12-28 weeks), two had delayed union that required bone graft and union at 28 and 32 weeks. Malalignment occurred in five cases. Sixty-two fragments were fixed with three screws-40 in cluster and 22 in separated positions. Ten fragments were fixed with four screws-eight in cluster and two separated. Broken screws were found in three cases; all were in the group with three screws fixed in cluster group. MIPO of the femoral shaft fracture is an alternative treatment in the patient where intramedullary nailing is contraindicated. Malalignment is the common complication that must be carefully evaluated intraoperatively. We recommend using at least three separated screws in each fragment to reduce the risk of screw breakage. © 2008 Springer-Verlag.